"I'm Not Thinking about It to Understand It, I'm Thinking about It to Do It": Students' Sensemaking Experiences from the Modern Dance Classroom. Issue 1 (2nd January 2023) - Henley, Matthew; Conrad, Robin
ABSTRACT: This research explores the question: How do students describe their own sensemaking practices in the postsecondary modern dance classroom? Based on semi-structured interviews with three postsecondary dance students at the first author's institution, this article presents individual accounts that capture students' perceptions of making sense of new movement material in a modern dance class. From the accounts, three themes emerged: implicit curriculum, the embodied mind, and the role of attention. We discuss these themes in relation to existing literature from learning theory and dance education and offer implications for creating an equitable learning environment. This research, which blends teacher self-study and qualitative inquiry, is intended to inform departmental practice and contribute situated perspectives to theories of learning in dance.